Keratoconus: a cross-sectional descriptive study looking at disease severity of patients presenting to the corneal clinic at St John eye hospital in Soweto (as part of the University of the Witwatersrand academic circuit) Johannesburg, South Africa - Mitha, Fathima (My University, 2019)
Purpose: To assess the disease severity of keratoconus population at St John Eye Hospital (a single tertiary eye care centre) and to describe the demographic profile of the population. Method: A cross-sectional descriptive study was conducted at St John Eye Hospital over a period of 18 months. 105 patients were enrolled. Patients completed questionnaires regarding demographic data. File audits and clinical examinations were then conducted with keratometry and pachymetry readings and Scheimpflug imaging. Results: 105 patients were enrolled. The majority of participants, 56.2% (n=59) had advanced keratoconus (Amsler-Krumeich Classification). Prior to refractive correction the majority of patients were classified as severe to total blindness. With refractive correction, 41% (n= 43) and 40.4% (n=42) of patients had moderate improvement in their visual acuities in their right and left eyes respectively. Patients who had no improvement in their visual acuities in their right eyes represented 24.8% (n=26) and left eyes 26.7% (n=28), despite attempted refractive correction. 59% of the study group were female and 93.3% were of black ethnicity. 47% of patients presented to St John Eye Hospital for the problem of poor vision. 84.8% of patients had a history of ocular allergy. 18 individuals had had prior keratoplasty with 29 (27.6%) of the study population awaiting keratoplasty. Conclusion: Opportunistic health promotion, through screening of patients with vernal keratoconjunctivitis will assist in detecting early asymptomatic disease in predisposed individuals. If the disease is detected early, collagen cross-linking may prove to be essential to halt progression. Despite advances made in refractive correction, increased availability of keratoplasty and attempts to halt the progression of the disease, there remains a large burden of morbidity. With a high burden of severe keratoconus, and a substantial backlog in patients awaiting keratoplasty, measures to facilitate keratoplasty are needed. Factors hampering keratoplasty access include availability of tissue and financial and system constraints.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Medicine. Johannesburg, 2019